Changes in the Identity of Contemporary Man in the Context of Neoliberalism - Michałowska, Danuta Anna (Sensus Historiae, 2020)
The aim of the paper is to present the ethical aspects of neoliberalism that influence the changes of identity of contemporary man. The neoliberal discourse creates a specific vision of the essence of humanity which is homo neoliberalis, defined by homo oeconomicus and homo consumens. The legitimisation of the neoliberal vision of human being does not promise a positive outcome for the democratic society. Neoliberalism considered in terms of ideology, is present in contemporary social thought and noticeable in everyday institutionalized education reality, shaping the identity of young people. Criticism of neoliberal implications for young people’s education and identity formation is a turning point in the search for a new vision of contemporary human identity; important in building a democratic society.